Register Pekerja Divisi Sample di PT. Yongjin Javasuka Garment Sukabumi: Kajian Sosiolinguistik - Aisyah, Adinda Destiana; Nasrul, Nasrul (Universitas Lampung, 2024)
This study aims to describe the form, function, and meaning of the sample Division workers register at PT. Yongjin Javasuka Garment Sukabumi. This study uses qualitative descriptive method. The Data obtained in this study in the form of words and phrases included in the register of workers. Methods and techniques of presentation of data analysis using informal presentation methods. The results showed that the register used by the workers of the sample division at PT. Yongjin Javasuka Garment Sukabumi which is engaged in the apparel manufacturing industry, consists of an open selingkung register and a limited selingkung register. As for the open-ended register, there is a register data that does not only have one meaning and field in accordance with the definition of open-ended register. In addition, there are data registers that have only one meaning and relate to only one field, in accordance with the definition of a limited scope register. Meanwhile, the register function consists of directive and referential functions. While the meaning contained in the register data, consisting of lexical meaning, grammatical, meaning of words, and terms.Keywords: manufacturing industry, register, sociolinguistics